Islamic And Technological Factors In Islamic Bank Customers’ Satisfaction - Herlina, Adek; Rahmany, Sri; Hendarsyah, Decky (Fakultas Agama Islam, Universitas Ibn Khaldun Bogor, 2024)
This study examines the influence of Islamic branding, Islamic service quality, internet banking, mobile banking, and automatic teller machine (ATM) facilities on Islamic bank customers’ satisfaction. This study adopted a quantitative approach with primary data sources in questionnaires obtained from 332 respondents and analyzed using multiple linear regressions. The main result shows that Islamic branding, Islamic service quality, internet banking, mobile banking, and ATM facilities affect Islamic bank customers’ satisfaction. The dominant factor influencing Islamic bank customers’ satisfaction is internet banking. This study can complement existing theories and be used as a reference in implementing Islamic banking market development strategies. Meanwhile, from a managerial perspective, this study can be used as a reference for improving brand image and quality of service in an Islamic way, as well as technological facilities.